AN ANALYSIS OF ERRORS MADE BY ENGLISH LANGUAGE EDUCATION DEPARTMENT STUDENTS IN ENGLISH PARAGRAPH WRITING - Nurlaily Nurlaily (JALL (Journal of Applied Linguistics and Literacy), 2022)
This research aims to analyze grammatical and mechanical errors made by English Language Education Department students in Batam City in writing a summary and response paragraph. This study applied a mixed-method approach to analyze the data. This study used documentation and a checklist as tools for collecting data which was the students' writing. The data illustrated that in grammatical aspects of writing, there are six types of errors: noun, pronoun, verb, article, prepositions, and subject-verb agreement. In mechanical elements, the students made errors in punctuation, spelling, and capitalization. It was also found that the most dominant error in grammatical features is in the use of articles. Meanwhile, punctuation had the highest percentage of mechanical errors (30% of the errors), which is the most prevalent in the students' writing. These results indicate that the students need to pay more attention to grammar and mechanics in their writing.